Hydrological responses in equatorial watersheds indicated by Principal Components Analysis (PCA) - study case in Atrato River Basin (Colombia) - Betancur, Sebastian Balbin [UNESP]; Gastmans, Didier [UNESP]; Vasquez, Katherine Vasquez; Santarosa, Lucas Vituri [UNESP]; Santos, Vinicius dos [UNESP]; Kirchheim, Roberto Eduardo (Assoc Brasileira Recursos Hidricos-abrh, 2020)
The Atrato river basin is located in the Pacific fringe of Colombia, region with one of the highest precipitation rates in the world. The main purpose of this study is to determine the dominant processes in the hydrological responses along 17 sub-basins within the basin using principal component analysis. Watersheds located at the headwater presented a fast or medium response to the precipitation events, while higher flow homogeneity was observed in watersheds located at the lower portions of the basin. Three principal components were responsible for explaining 85.18% of the total variance. The component PC1 revealed the largest contributions for low flow behavior, being associated to precipitation, characteristic discharge values, compactness index, soil coverage and soil coarse textures. The component PC2 was assigned to the geological variables, fine and average texture soil and the average basin slope. Finally, the component PC3 has shown to be related to high flow patterns (maximum characteristic discharge values Q(5) and Q(1)), igneous rocks and length of the basin. Highest specific discharge was associated to alluvial deposits and forest cover, whereas the slope was considered determinant for the run-off generation.
Keywords: Atrato river basin; Flow duration curves; Principal component analysis; Colombia